Biodiversity: Farmers teaching farmers - Lenoir, Miep (Technical Centre for Agricultural and Rural Cooperation, 2009)
After researchers in Burkina Faso identified the best crop varieties for the Sissili region, a local organization, FEPPASI, introduced ICTs to inform farmers and explain new growing techniques. As a result, production is up to nine times greater than before.